Radiotrophic fungi and their use as bioremediation agents of areas affected by radiation and as protective agents (Research, Society and Development, 2025)
Nuclear waste, from nuclear fuel and nuclear accidents, represents a great risk to the environment and human beings, causing several problems such as malformation, and cancer, it can turn areas uninhabitable, causing changes in the fauna and flora of entire areas. In the search for a more effective way to deal with such contaminants, it is proposed the use of radiotrophic fungi, such as those found inhabiting the reactor of Chernobyl in Ukraine, the poles, and the international space station, due to their high resistance to these contaminants, the power of absorption of ionizing radiation and the deposition of radioisotopes in their cell walls, making possible the removal of them from the environment in which they are found, as well as the consumption of organic matter, such as the graphite present in the reactor number 4 of Chernobyl. Another property to be explored is the protective use of these organisms to reduce the incidence of ionizing radiation in areas of interest and protect human beings. Therefore, this research aimed to study the mechanisms of action and the effectiveness of these bioremediation agents. The research consisted of a bibliographical review, using database resources and the library collection of the University of Passo Fundo, totaling 56 materials (articles and books), after compilation and evaluation, it can be concluded that radiotrophic fungi are promising as bioremediation agents, with potential for protecting equipment, human beings and as biosensors to detect the presence of ionizing radiation.